Prenatal diagnosis – a comparison of rapid testing by QF-PCR versus full karyotyping in the Scottish population. (18th April 2012) - Wu, P; Crawford, L; McConnell, C; Gibson, JL; Cameron, AD
Abstract : Current health policy encourages the use of rapid trisomy testing rather than full karyotype analysis. We compared the results of QF-PCR with full karyotyping via a retrospective audit. Between 01/11/09 and 31/10/11, 1726 CVS or amniocentesis samples from prenatal diagnostic procedures were received in the regional genetics laboratory which serves a population of 3 million. Main referral reason was due to abnormal scan (52%), followed by increased risk at second trimester screening (31%). Family history of chromosomal anomalies (7%) and maternal age (5%) were less common indications. Three cases had inadequate sample for culture, 1 failed culture and 1 was not set up. Abnormal karyotype was seen in 181 samples: 71% of abnormalities were correctly identified at the time of QF-PCR. Approximately 50% had trisomy 21, 25% had trisomy 18 and the remainder had Turner's syndrome, 69 XXX, or trisomy 13. In 51 cases, QF-PCR did not detect the abnormality seen at full karyotyping. Of these, 16 cases had balanced translocation or inversion and 15 had normal ultrasound examinations. Thirteen had unbalanced changes and 10 of these also had abnormal scans. Due to referral reasons (e.g. maternal age or biochemical screening), sex chromosomes were not always examined at QF-PCR. Fourteen cases of XO / XXX / XXY were missed. There were 4 samples with mosaicism but only 1 case also had an abnormal scan. Valuable additional information can be obtained by full karyotyping. However, in those with severe chromosomal abnormalities, structural anomalies are often seen on ultrasound examination.